The relationship between intrapersonal factors and consumers' purchase intentions on hedonic products with sustainable packaging: The mediating role of green brand attitude and attachment - Alloso, Angelica Samantha T. (Animo Repository, 2022)
In 2017, global plastic pollution surpassed 348 million tons. The growing amount of plastic waste in the environment is attracting more global attention as more consumers are becoming more eco-conscious in their Purchase Intention. The study aims to assess the relationship between Intrapersonal Factors and Purchase Intention, and the mediating effect of Green Brand Attitude and Green Brand Attachment on hedonic products with sustainable packaging. The researchers desired sample size of 260 respondents. The respondents were consumers of Mayumi Organics, indicating that they have either bought or used the product. Descriptive statistics, correlational analysis, simple linear regression, and mediated regression analysis were used to analyze the quantitative data. The researchers of this study used a confidence level of 90% and a margin of error of 5% to analyze the data. The results of the study indicate that there is a significant relationship between Intrapersonal Factors and consumer’s Purchase Intention on hedonic products with sustainable packaging. The results also showed that Green Brand Attitude and Green Brand Attachment mediates the relationship between the Intrapersonal Factors and the consumer's willingness to purchase hedonic products with sustainable packaging. Therefore, the researchers concluded that Mayumi Organics must continue their environmental efforts through utilizing sustainable packaging.